The slave-girl from Jerusalem - Lawrence, Caroline (London : Orion Children's Books, 2009)
Flavia, Jonathan, Nubia, and Lupus work together within the rules of the ancient Roman legal system to prove the innocence of Hephzibah, a slave in a wealthy household who has been accused of murder, but the witnesses are killed before they can testify before the magistrate.
5.3
5-8
Keywords: Murder -- Juvenile fiction; Slaves -- Juvenile fiction; Historical fiction; Murder -- Fiction; Mystery and detective stories; Slaves -- Fiction; Historical fiction; Homicide -- Fiction; Mystery fiction; Slaves -- Fiction; Rome -- History -- Empire, 30 B.C.-284 A.D. -- Juvenile fiction; Rome -- History -- Empire, 30 B.C.-284 A.D. -- Fiction; Rome -- History -- Fiction; Historical fiction; Mystery fiction